Chronic rhinosinusitis: medical versus surgical management - Patel, Seema; Rekhade, Tanvi S.; Pawar, Rameshwar T.; Nitnaware, Ashok Z. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Management protocols of chronic rhinosinusitis (CRS) recommend initial treatment with maximal medical therapy with surgery reserved for refractory cases. Literature comparing the effectiveness of these two treatment modalities is limited. The purpose of this study was to compare the outcome of medical and surgical management for CRS. Methods: This was a prospective cohort study. Patients registered for the study were diagnosed as CRS based on history, clinical examination and investigation findings. All patients were initially subjected to medical management for 3 weeks and refractory cases were then subjected to surgical intervention. Subjective and objective improvements assessed with SNOT-22 score and Lund-Kennedy (LK) score respectively were analysed statistically. Results: Out of the 100 patients registered for the study, 37% had nasal polyposis while 63% were without polyposis. When subjective and objective improvements were compared between groups receiving medical management alone and those receiving combined management, the difference was not found to be statistically significant (p<0.05). Conclusions: Although the decision regarding treatment modality to be used in CRS should depend on individual case, all cases can be subjected to a maximal medical therapy initially while reserving surgery for cases which do not improve.